An in vitro model system for testing chemical effects on microbiome-immune interactions – examples with BPX and PFAS mixtures - Fischer, Florence; Pierzchalski, Arkadiusz; Riesbeck, Sarah; Aldehoff, Alix Sarah; Castaneda-Monsalve, Victor Alfonso; Haange, Sven-Bastiaan; von Bergen, Martin; Rolle-Kampczyk, Ulrike Elisabeth; Jehmlich, Nico; Zenclussen, Ana Claudia; Herberth, Gunda (Frontiers in Immunology, 2024)
More than 350,000 chemicals make up the chemical universe that surrounds us every day. The impact of this vast array of compounds on our health is still poorly understood. Manufacturers are required to carry out toxicological studies, for example on the reproductive or nervous systems, before putting a new substance on the market. However, toxicological safety does not exclude effects resulting from chronic exposure to low doses or effects on other potentially affected organ systems. This is the case for the microbiome-immune interaction, which is not yet included in any safety studies.The aim of the present study was to use a high-throughput in vitro model to shed light onto elucidate the potential effects of environmental chemicals and chemical mixtures on microbiome-immune -interactions. Therefore, a simplified human intestinal microbiota (SIHUMIx) consisting of eight bacterial species was cultured in vitro in a bioreactor that partially mimics intestinal conditions. The bacteria were constantly continuously exposed to mixtures of representative and widely distributed environmental chemicals, i.e. bisphenols (BPX) and/or per-and polyfluoroalkyl substances (PFAS) at concentrations of 22 µM and 4 µM, respectively. Furthermore, alterations changes in the immunostimulatory potential of exposed microbes were investigated using a co-culture system with human peripheral blood mononuclear cells (PBMCs).The exposure to BPX, PFAS or their mixture did not influence the community structure and the riboflavin production of SIHUMIx in vitro. However, it altered the potential of the consortium to stimulate human immune cells: in particular, activation of CD8 + MAIT cells was affected by the exposure to BPX-and PFAS mixtures-treated bacteria.The present study provides a model to investigate how environmental chemicals can indirectly affect immune cells via exposed microbes. It contributes to the much-needed knowledge on the effects of EDCs on an organ system that has been little explored in this context, especially from the perspective of cumulative exposure.